Hypocholesterolemic Effect of Beet Root Extract (beta vulgaris) in Rats - yuniarti, christina ary; Sri Ratna Rahayu, Rr; Yuniastuti, Ari (Public Health Perspective Journal, 2019)
Dyslipidemia is a disorder of lipid metabolism that causes narrowing of blood vessels. Risk factors for coronary heart disease are characterized by an increase in cholesterol. Thus, prevention needs to be done by changing a balanced diet that is eating one fruit and vegetable, one with beet root that has a high antioxidant content. The purpose of this study was to examine the activity of beet root extract on rat cholesterol levels. This research method is experimental with post test design only randomized control group design. Treatment at a dose of 100 mg / kg, 200 mg / kg combined with 0.18 mg / kg simvastatin. The sample in this study was Wistar strain male rats aged 2-3 months with a weight of 100-200 grams, the technique of random sampling using the formula Federer as many as 5 animals / group and divided into 7 treatment groups. Beet root extract and atherogenic feed were given for 35 days. Cholesterol levels were examined by the CHOD-PAP (Cholesterol Oxidase-Peroxidase Aminoantipyrine Phenol) method using a clinicon 4010 photometer. Data were analyzed using the Kruskall Wallis and Mann Whitney tests. The effect of beet root extract activity on reducing cholesterol levels at a single dose of 100 mg/kg BW of 17.40% (p-value = 0.673), single dose 200 mg / kg BW of 21.59% (p-value = 0.009), combination dose of 100 mg / kgbb of 7.10% (p value = 0.009), a combined dose of 200 mg / kgbb of 18.65% (p value = 0.347). Beet root extract is effective in reducing rat cholesterol at a dose of 200 mg/kg BW.Ã‚Â